Low carbon footprint building materials using industrial waste - Lam V. Tang; Dung T. Nguyen; Boris I. Bulgakov; Olga V. Aleksandrova (Нанотехнологии в строительстве)
Introduction. The possibility of producing construction materials in Vietnam based on man-made waste with a low carbon footprint and capable of absorbing carbon dioxide is being considered in order to achieve zero greenhouse gas emissions by 2050. To date, insufficient attention has been paid to the search for a solution to this problem. Methods and materials. Studies were conducted to assess the possibility of obtaining a ”green“ cement-free concrete material using local industrial and agricultural waste in the form of fly ash and bottom slag from the Green Star incineration plant, alumina sludge, ceramic waste, lime powder and coconut fiber combined with a special activating agent. an alkaline solution. The average density, compressive strength, and water absorption of the developed cement-free concrete were determined on cube samples measuring 100×100×100 mm in accordance with the requirements of current Vietnamese standards. The ability of the resulting concrete to absorb carbon dioxide was evaluated using the developed method by measuring the mass of carbon dioxide absorbed by concrete samples. Results and discussion. The average density of the developed concrete is 1950 kg/m3; compressive strength at the age of 28 days is 7.5–11.5 MPa; water absorption is 8–10% by weight. The main advantages of using cement-free concrete of the developed composition include reducing the carbon footprint due to the abandonment of the use of Portland cement, the ability of concrete to absorb carbon dioxide and the possibil ity of recycling high-tonnage man-made waste during its manufacture. Conclusion. The results of the conducted research show that the use of the developed cement-free ”green“ concrete for the manufacture of building products and structures in Vietnam will allow to recycle about 1.1 tons. high-tonnage industrial waste per 1 cubic meter and absorb 10–13 kg of carbon dioxide during operation. This will contribute to the implementation of the planned course for the ”green“ transformation of Vietnam's economy into a sustainable closed-loop economy.